Relação da rigidez e do toque articular com a Diabetes mellitus do tipo 2 e a neuropatia periférica - Ferreira, Jean de Paula (2020)
The literature indicates a strong relationship between musculoskeletal losses and the incidence of type 2 diabetes mellitus (DM2), and it is also unclear whether DM2 affects the passive properties of the musculoskeletal system, increasing the muscle stiffness and impairing the function of these individuals. Objective: To analyze whether concentric and isometric torques can distinguish between individuals with DM2 and peripheral diabetic neuropathy (DPN) from individuals without DM2 with the same age and anthropometric characteristics, and also to analyze the passive torque and passive stiffness in DM2 individuals, with and without NDP at the knee and ankle flexion and extension compared to individuals without DM. Methods: Of the 88 participants, 29 were controls, 59 with DM2 (23 with and 36 without DPN). Glycemic control was determined by HbA1C and DPN by the Michigan Neuropathy Screening Instrument (MNSI). Concentric and isometric torque during knee and ankle flexion and extension were assessed by isokinetic dynamometry and torque suitability by principal component analysis (PCA). The identified variables were further used in a cluster analysis (k-means). Stepwise regression was applied to investigate factors associated with HbA1c and MNSI scores. For passive torque analyses, three groups of men (n=49) of similar age were studied, 17 with DM2 without DPN, 15 with DM2 and DPN, and 17 control subjects without DM2. Knee flexion and extension passive torque as well as ankle dorsiflexion and plantar flexion were assessed on an isokinetic dynamometer, followed by passive torque and passive stiffness calculation. The absence of muscular activity during the tests was determined by electromyography (EMG). Results: Concentric knee flexion and extension and isometric ankle extension torques characterized 88.59% of the individuals, forming Cluster 1 (n=29 controls) and Cluster 2 (n=59 DM2). HbA1c was associated with lower torque and higher IL-6, and MNSI score with lower torque and higher TNF-α and IL-6. Subjects with DM2 and DPN exhibited greater knee extension passive stiffness (p<0.01) as well as increased passive torque and stiffness during dorsiflexion and plantar flexion (p<0.04) at 5o /s when compared to controls and those with DM2 without DPN. Conclusion: Concentric knee and isometric ankle torques discriminated between subjects with and without DM2. However, knee and ankle torque reductions associated with DPN, poor glycemic control, and subclinical inflammation were not sufficiently significant to differentiate between DM2 individuals with and without DPN. Individuals with DM2 and DPN present higher knee and ankle stiffness and passive torque in comparison to those with DM2 without DPN and the controls. The mechanical impairments in ankle viscoelastic structures were most evident and more easily assessed at low speeds.